Mycorrhizal status of alpine plant communities on Mt. Maedake Cirque in the Japan South Alps - Kagawa, Atsushi; Fujiyoshi, Masaaki; Tomita, Miki; Masuzawa, Takehiro (National Institute of Polar Research, 2006)
P(論文) To clarify the mycorrhizal status of alpine plants, we sampled roots of 33 species from 15 families growing on Mt. Maedake Cirque in the Japan South Alps. Ericoid mycorrhiza, ectomycorrhiza and arbuscular mycorrhiza (AM) were observed in the study site. Colonization classified as ericoid mycorrhizal was observed with Phyllodoce aleutica, Tripetaleia bracteata, Vaccinium uliginosum, Rhododendron aureum, Arcterica nana and Shortia soldanelloides f. alpina, and ectomycorrhizal colonization with Pinus pumila and Polygonum viviparum. AM plants were found in species belonging to the following families: Compositae, Geraniaceae, Ranunculaceae, Rosaceae, Gramineae, Liliaceae, Violaceae, Crassulaceae, Gentianaceae and Campanulaceae. AM was the predominant mycorrhizal type in the study site and average colonization levels of AM fungi were within a wide range of 1.2 to 76.1%. In conclusion, mycorrhizal associations were observed in most (91%) of the plant species examined under the severe climate conditions of the study site. departmental bulletin paper